Cultures of fear : a critical reader - Smith, Danielle Taana; Linke, Uli (Colección de libros electrónicos de ULoyola, 2009)
In this powerful new book, sociologist David L. Altheide demonstrates how the mass media constructs a politics of fear in America. He argues that politicians and decision-makers bear much of the blame for the promotion of fear among citizens, resulting in the loss of civil liberties in return for greater protection. From a social interactionist perspective, Altheide presents his thesis that fear-as-entertainment informs the production of popular culture and news, generates profits, enables political decision-makers to cynically manipulate citizens, and can lead to major institutional changes, even war.